The Impact of Risk Criteria on the Continuity of Transactions of Companies Listed on the Tehran Stock Exchange, Emphasizing the Effective Role of Risk Management - Elahe Kharaziyan Motlagh; Seyed Hesam Vaghfi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Investors usually react to risk, and risk criteria affect their investment decisions. The continuity of stock trading is very important for investors. Therefore, the current research aims to investigate the impact of risk criteria on the continuity of transactions of stock exchange companies, emphasizing the effectiveness of risk management from 2019 to 2020.Methodology: The multivariate regression method and financial information of 107 companies accepted in the Tehran Stock Exchange were used to test the research hypotheses. The research method is inductive-deductive, in which the theoretical foundations and background were collected through the library, articles, and the internet. These were used to test the research hypotheses by applying appropriate statistical methods to generalize the results. The financial data has been collected in Excel software to form a database and then analyzed using EViews software version 12 to test the research hypotheses.Findings: The study showed that the risk criteria, according to the theoretical foundations of the research, aim to reduce the continuity of the company's transactions, and also risk management has a significant and direct impact on the relationship between systematic risk, financial risk, and stock price risk with the continuity of the company's transactions, but the effectiveness of the management. The risk of the relationship between the risk of financial crisis and the continuity of transactions was not confirmed.Originality/Value: No research has been done on Iran's transaction continuity and risk problem, even though investors and company managers usually consider both criteria. The existence of an effective risk management system can also have informational content regarding the risk and continuity of transactions. This issue has also been examined in the current research. According to the results of the study, it can be said that risk criteria for investors have informational content, so managers who prioritize the liquidity of their company's shares should act in their decisions in such a way that the amount of debt to assets in be the optimal limit or behave in such a way that the company does not fall under the problems of the financial crisis.